Energy mismatch in Chinese industrial enterprises: A stochastic frontier approach - Junzhe Hu; Juntao Du; Yingsheng Shi; Xue-Li Chen; Xiangzheng Deng; Malin Song (Sustainable Futures, 2025)
Energy is an indispensable and critical driver of global economic development. China's crude energy consumption pattern and the increasingly serious energy mismatch (EM) problem of industrial enterprises, addressing mismatches in the marginal output of energy factors, have become a formidable challenge. This study utilized panel data of 2199 industrial enterprises in China from to 2005–2015 to measure energy output elasticity, the EM coefficients of industrial enterprises, and their influencing factors via the stochastic frontier approach (SFA). The results show that (1) between 2005 and 2015, the degree of EM within the entire industrial sector increased under the influence of the financial crisis. (2) The overall characteristics of EM in China from 2005 to 2015 were primarily manifested in the rapid growth of total energy consumption, irrational energy structure, low energy utilization efficiency, imperfect energy pricing mechanisms, and unsound energy management systems. (3) Corporate profitability and employees have significant negative effects on the EM of industrial corporations, leading to an increase in energy distortion. Financing constraints, net fixed assets, and enterprise scale have a significant positive impact on EM, which is conducive to improving the EM phenomenon.